POLA PENGGUNAAN OBAT UNTUK PENDERITAGAGAL GINJAL AKUT DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM PUSAT (RSUP) DR. SARDJITO YOGYAKARTA TAHUN 1997-2001 - Hanifah, Suci (Jurnal Ilmiah Farmasi, 2004)
ABSTRACTDrug Utility Review for ARF’ patients of Internal Unit, Sardjito’s hospital was examed. Itinvolved 109 ARF’s patients. Medical Record Unit reported that this number was 0,12% of alldisese i.e. 93.445 case in 2001. The level was 93rdfrom 945 kind of disease. It was studied bynonanalitical descriptive design. using notes of Medical Record system. Collecting of data byretrospektive methode. This research was aimed to study the Drug Utility Review for ARF’spatients, especially to study ; drug variation included kind and class of drugs, route ofadministration, variation drug number, length of stay, and regimen dosage of drugs. To complete it,mortality persentaged was reported. The result of the study showed that ARF’s patients got somany variation of drugs. Using of antibiotic, diuretic, and electrolit was the most case. It conformedto Health Care Standard in Sardjito’s hospital. The others was aimed to simptomatical drugs i.e.antihypertensi, cardioasculer drugs, analgetic, antiemetic, multivitamin, laxan etc. It depended onsymptoms and complication of patients. Variation of number between 1-24. The average numberwas 7,7 drugs. It tended to use new generation of antibiotic and combinatins antibiotic, as indicatorof extravagant prescibing. Route of administratin by orally in most case and 38 % by injection.Injection route so indicate extravagant prescibing except on emergency care. The others used bysublingual and suppositoria. Length of stay averaged 12,52 days. Mortality persentaged was 22%.Key words : Drug Utility Review, ARF, Medical Record,Extravagant Prescribing